2011
DOI: 10.1016/j.canlet.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CRKII increases migration and invasive potential in oral squamous cell carcinoma

Abstract: CT10 regulator of kinase (CRK) was originally identified as an oncogene product of v-CRK in a CT10 chicken retrovirus system. Overexpression of CRKII has been reported in several human cancers. CRKII regulates cell migration, morphogenesis, invasion, phagocytosis, and survival; however, the underlying mechanisms are not well understood. In the present study, we evaluated the possibility of CRKII as an appropriate molecular target for cancer gene therapy. The expression of CRKII in 71 primary oral squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…Since the gene loci of CRKL and CRK are completely distinct [3,27], the functional priority for CRKL is likely to be important for HNSCC-carcinogenesis at a genetic level. Here we also explored similar expression profiles of both CRKL and CRK in HNSCC by immunohistochemistry, although Yamada et al [13] indicated the prominent expression and function of CRKII in HNSCC. They employed the CRKII-specific antibody which does not recognize CRKI and revealed the clinicopathological significance of CRKII in HNSCC, including clinical stage and patient's survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the gene loci of CRKL and CRK are completely distinct [3,27], the functional priority for CRKL is likely to be important for HNSCC-carcinogenesis at a genetic level. Here we also explored similar expression profiles of both CRKL and CRK in HNSCC by immunohistochemistry, although Yamada et al [13] indicated the prominent expression and function of CRKII in HNSCC. They employed the CRKII-specific antibody which does not recognize CRKI and revealed the clinicopathological significance of CRKII in HNSCC, including clinical stage and patient's survival.…”
Section: Discussionmentioning
confidence: 99%
“…CRK was shown to play an essential role in the malignant potential of various human tumors including ovarian cancer, synovial sarcoma, glioblastoma, and head and neck squamous cell carcinoma (HNSCC) [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the CT10 regulator of kinase (CRKII), which has been found in several human cancers, is associated with an aggressive phenotype of oral squamous cell carcinoma. CRKII regulates cell migration, morphogenesis, invasion, phagocytosis and survival (Yamada et al 2011). Two isoforms, CrkI (SH2-SH3) and CrkII (SH2-SH3-SH3), differ in their transforming activity, which is high for CrkI and low for CrkII.…”
Section: Regulationmentioning
confidence: 99%
“…Such vital processes as migration and invasiveness (Yamada et al 2011), actin reorganization induced by extracellular signals (Antoku and Mayer 2009), shaping spines (Sheng and Kim 2000;Ehlers 2002), among others take a central role when new treatments rely on an understanding of cellular control mechanisms.…”
Section: Regulationmentioning
confidence: 99%
“…CrkI is a more potent transforming gene than CrkII and CrkL in part because, like v-Crk, it lacks a C-terminal regulatory phosphorylation site (3). Overexpression of Crk and CrkL has been reported in several human cancers, including oral squamous cell carcinoma (5), ovarian carcinoma (6), colon cancer (7), lung cancer (8,9), breast cancer (10,11), gastric cancer (12), and glioblastoma (13,14). Reduced expression of either Crk or CrkL by RNA interference-mediated knockdown lowered the in vivo tumor formation of human ovarian (15), synovial sarcoma (16), glioblastoma (14), breast cancer (10), head and neck squamous cell carcinoma (17), and rhabdomyosarcoma (18) cell lines.…”
mentioning
confidence: 99%